İftira suçu (TCK M. 267) - Kurt, Derya Hilal (My University, 2020)
Bu sayılı Türk Ceza Kanununun ikinci kitabını oluşturan “Özel Hükümler” in dördüncü kısmında yer alan “Millete ve Devlete Karşı Suçlar ve Son Hükümler” üst başlığının, ikinci bölümünde yer alan “Adliyeye Karşı Suçlar” alt başlığı altında 267nci maddede düzenlenen “İftira” suçu ceza hukuku disiplini bakış açısıyla incelenmektedir. Üç ana bölümden oluşan çalışmamızın ilk bölümünde iftira suçuna ilişkin öncelikle genel bilgilendirme yapılarak, suçun tarihsel süreci Türk Hukuk Sistemindeki gelişimi ve mukayeseli hukuktaki düzenleniş biçimi ele alınmıştır. Akabinde iftira suçunun “Adliyeye Karşı Suçlar” başlığı altında düzenlenen benzer suçlardan farkı üzerinde durulmuş ve böylelikle korunan hukuki menfaatin ne olduğu hususu doktrindeki tartışmalarla birlikte açıklığa kavuşturulmaya çalışılmıştır. Çalışmamızın ikinci bölümünde ise iftira suçunun kapsamı ve unsurları açıklanmış, hukuka uygunluk nedenlerinin iftira suçu bakımından uygulanıp uygulanamayacağına kısaca değinilmiştir. Suçun tüm unsurlarıyla oluşması halinde failin cezalandırılabilmesi yönünden kusurluluk durumu irdelenerek, nihayet cezaya etki eden nedenler başlığı altında suçun neticesi sebebiyle ağırlaşmış halleri ile etkin pişmanlık kurumuna yer verilmiştir.Nihayet üçüncü bölümde ise suçun özel görünüş biçimleri ile yaptırım ve muhakeme hususları da açıklanarak suça ilişkin klasik metot kullanılarak yapılan inceleme tamamlanmıştır. İftira suçu bakımından özellik arz eden “hükmün ilanı” ile “zamanaşımı” konularının ayrı bir başlık altında incelenmesi tercih edilmiştir. Çalışmanın genelinde, iftira suçuna ilişkin olarak güncel literatür ve Yargıtay içtihatlarından faydalanılmıştır.

In this postgraduate thesis, the crime of calumny regulated in the Article 267, which is under the subheading called “Offences Against Judicial Bodies or Court” and located under the second part of the “Offences against Nation and State and Final Provisions”, which is the fourth chapter of the “Volume II-Special Provisions” of the Turkish Criminal Code-Law Nr. 5237, has been examined with the view of criminal law discipline. In the first part of the study, which consisted of three main parts, after primarily the general information regarding the crime of calumny has been given, the historical process of the crime has been discussed together with its development in the Turkish Legal System and with its form of arrangement in the comparative law. Subsequently, the differences of the calumny from other crimes regulated under the subheading of “Offences Against Judicial Bodies or Court” have been emphasized, and thus, the question of which legal benefit is protected has been tried to be answered with the help of the discussions held in the doctrine.In the second part of the study, the scope and the elements of the crime of calumny have been explained, then, whether the compliance reasons with the law can be applied in terms of calumny has been briefly touched on. After examining the culpability of the perpetrator in terms of his/ her punishability in a condition when the crime occurs with its all elements, the circumstances ofan offenceaggravated as a result of injurious consequences and the effective remorse have been given place under the title of reasons affecting the punishment.Finally, in the third part, by explaining the special appearance forms of the crime and the matters of penal sanctions and procedure, the study conducted with the classical methodology regarding the crime has been completed. The “announcement of the verdict” and the “limitation periods” that are important topics regarding the crime of calumny have been preferred to be explained separately.Throughout the study, recent editions of the books related to the crime of calumny, fundamental sources, scientific articles, and the Supreme Court practices have been utilized.
Keywords: Basın ve Yayın Yolu ile İftira; Calumny; Complaint; İftira; İhbar; Kamu hukuku; Maddi iftira; Material Calumny; Notification; Public law; Relevant and Competent Authorities; Şikâyet; The Crime of Calumny Through the Press or Broadcasting; Yetkili Makam